ANALYSIS OF TWITTER USER SENTIMENTS ON INDEPENDENT CURRICULUM INDONESIA - Fahmi Cholid; Suparman; Ngatma’in; Insani Wahyu Mubarok (Universitas Muhammadiyah Surabaya, 2024)
Education is a very important aspect in various lives, this cannot be separated from the magnitude of the role and positive impact caused by the advancement of an education system. The world of education is an effort to improve the quality of human resources in terms of thought and expertise. Education is the main key for a country to excel in global competition. Education is always related to the curriculum. The curriculum is a tool used to achieve educational goals so that it can be said that the curriculum is a reference in the process of organizing education in Indonesia. The Indonesian education curriculum has been changed or revised at least 10 times, namely in 1952, 1964, 1968, 1975, 1984, 1994, 2004, 2006, 2013. The latest curriculum in Indonesia, the independent curriculum is a time when teachers and students can or have freedom in thinking and also free in the burden of thought so that they can develop their educational potential. This research aims to classify the sentiment of Twitter users towards government policies regarding the independent curriculum into positive sentiment and negative sentiment. The method used by the Naïve Bayes Classifier (NBC) and Support Vector Machines (SVM). The Result shows that the percentage of positive sentiment is 47% or 451 tweets while the negative sentiment is 53% or 264 tweets.